Artificial Intelligence-Based Snakes and Ladders Game Media to Improve the Learning Outcome of Elementary School Students - Maharani, Maulida Putri; Kurotul Aeni (LPPM Undiksha, 2024)
The lack of practice of Pancasila values among elementary school students impacts students' low competency and character. This research aims to develop an AI-based snakes and ladders game media to improve student learning outcomes in material that emulates Pancasila behavior in Pancasila Education subjects. This type of research is development research (R&D). The model used in developing media is ADDIE. The research subjects are media experts and subject matter experts. Product trials were conducted in small groups with a sample of 28 students. At the usage test stage, it was carried out by all fifth-grade elementary school students. The methods used to collect data were observation, interviews, literature studies, and tests. The data collection instruments are questionnaires and test questions. The techniques used to analyze data are qualitative descriptive analysis and quantitative and inferential statistics. The research results, namely the product feasibility test results, are based on the validation results of media experts at 87.5% and material experts at 85%. The product practicality test was based on the teacher response questionnaire assessment of 87.5% and student response of 84%. The effectiveness test is based on the T-test results showing the influence of snakes and ladders-based game media. The results of the N-gain test show an increase in learning outcomes. It was concluded that the AI-based Snakes and Ladders game media can improve the learning outcomes of elementary school students.